EFISIENSI PEMASARAN BAWANG DAUN STUDI KASUS DI TANJUNG KARI KECAMATAN PULAU BERINGIN KABUPATEN OKU SELATAN (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2016)
Efficiency Analysis Marketing Research Objectives onion curry leaves in Tanjung Beringin Subdistrict Island Ulu Ogan Ogan is to calculate farm income scallion in Tanjung Kari and determine the marketing efficiency of scallion in the village of Kari Tanjung Beringin Subdistrict Island. The method used in this study is a survey method using a questionnaire as a data collection tool. Samples taken as many as 30 farmers sample of 210 members of the population of the percentage of the sample by 30 percent, collectors and collectors in the sub-district village 4 3. The results reveal receipt scallion Rp. 7,863,333 / ha / MT and the production cost of Rp. 5.85035 million / ha / MT, the obtained revenue of Rp 2,012,983 / ha / MT2. Marketing onion curry leaves in Tanjung Beringin Subdistrict Island has been streamlined, with a second channel that is marketing through traders subdistrict then directly marketed by wholesalers who then continued on the retailer directly at the consumer end is the best channel with a percentage of 5.4% efficiency.